Molecular evidence for Mycobacterium bovis infection in wild Chilean hawk (Accipiter chilensis) - Moroni, Manuel; Salgado, Miguel; Albornoz, Alejandro; Tejeda, Carlos; Alvarado-Rybak, Mario (Austral Journal of Veterinary Sciences, 2018)
The present study reports a case of tuberculosis in a juvenile Chilean hawk (Accipiter chilensis). Granulomas were identified in the liver, intestine and mesentery. Several of these granulomas contained acid-fast bacilli suggesting a mycobacterial infection through ingestion. Molecular diagnosis detected Mycobacterium bovis as etiological agent. Whether M. bovis infection in this Chilean hawk represents a risk for other wildlife, livestock or humans remains to be determined.